Risiko- und Resilienzbewusstsein: Empirische Analysen und erste konzeptionelle Ansätze zur Steigerung der Resilienzfähigkeit von Regionen - Martin Fontanari; Dirk Kredinger (readbox unipress, 2017)
– The consequences of terrorist attacks, financial crises, geopolitical interventions in North Africa and the Arab world, and the resulting instability of states and refugee flows to Europe, make the population vulnerable and create fear. Additionally, climate change, environmental degradation, energy erosion or demographic anomalies present new challenges for the state and the economy, which also impose a (tax) burden on citizens. Exogenous crises are complex and difficult to foresee and sometimes have a major negative impact on companies. Studies indicate that the concept of resilience is of central importance and that the need for change and adaptation must be strengthened in dealing with crises. The economic and consumption system is characterized above all by the elementary dependencies on the supply side. These, in turn, are closely linked to regional economies and related to regional economic cycles. A metropolis or a region has an original interest to minimize the crises susceptibility of the supply system and to build up appropriate resilience. An empirical survey to determine the current resilience level of selected basic supply providers in the region Trier and a survey of the demand side regarding the degree of crisis sensitivity and the degree of self-sufficiency show the extent to which the increase in crisis symptoms is justified by a systematic increase of the resilience capabilities and abilities of a region with its citizens and actors, and that a resilience-oriented regional management can take initial steps towards this (possibly unpopular) development.
Keywords: 330; Regionalentwicklung; Coping-Strategie; Infrastrukturversorgung; Öffentliche Dienstleistung; Deutschland; Trier (Region)